Pyrocene park : a journey into the fire history of Yosemite National Park - Pyne, Stephen J., 1949- (The University of Arizona Press, 2023)
"The book is a fire history of Yosemite National Park, with the Illioutte Basin watershed a specific focusing point of discussion, told via two interlocking narratives, historical and personal. It's a story of the role of fire in shaping the park and the human dramas within it, and the evolution of fire management philosophy as generations of stewards attempt to reconcile disparate ideas of wilderness and control in an iconic landscape. The major argument of the manuscript follows that wildfire has a long history within the Park and that historic human intervention into that fire has complicated the relationship greatly. Also, that the story is still evolving and has an uncertain future. Throughout, the author discusses elements of fire ecology, sociopolitical factors, and personalities who have contributed to shaping the current state of fire management in the Park"--